Evaluation of high sugar containing corn genotypes as viable feedstocks for decreasing enzyme consumption during dry-grind ethanol production - Zabed, H.; Faruq, G.; Boyce, A.N.; Sahu, J.N.; Ganesan, P. (Elsevier, 2016)
Requirement of costly enzymes (α-amylase and glucoamylase) for converting starch into glucose before fermentation is considered one of the cost increasing factors for corn ethanol. Enzyme consumptions can possibly be reduced during dry-grind ethanol production by increasing free sugar contents in corn kernels that will be released and fermented simultaneously with the product of starch hydrolysis, producing an additional amount of ethanol without consuming any enzyme. A comparative study was conducted to evaluate the effect of kernel sugars on enzyme requirement and yields of both hydrolysis and fermentation, using four high sugary corn genotypes (HSGs) and their parent field corns (PFCs). Enzymatic hydrolysis of the genotypes with four enzyme loads (1, 2, 3 and 4 kg MT-1 of dry corn) showed that HSGs produced higher proportions of reducing sugars (RS) in all conditions than PFCs did. Sufficient amounts of RS were produced by HSGs utilizing an enzyme load of 3 kg MT-1, whereas, PFCs consumed 4 kg MT-1 for their best yields. Likewise, HSGs produced higher concentrations of ethanol consuming lower amount of enzymes during fermentation. Therefore, HSGs could be considered as potential feedstocks for enhancing ethanol yield and reducing enzyme consumptions during dry-grind ethanol production.